(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2013)
Poly(vinyl alcohol)-zirconium compound hybrid nanofibers (precursors) were formed by electrospinning employing water as a solvent for the spinning solution. The precursors were converted into oxide (ZrO2), carbide (ZrC) or nitride (ZrN) nanofibers by heating them in air, Ar or N2 atmospheres. Monoclinic ZrO2 nanofibers with high-specific surface area were obtained by heat-treatment of the precursors in air. ZrC and ZrN nanofibers could be obtained below theoretical temperatures calculated from thermodynamics data.